Fire season modifies the perennial plant community composition through a differential effect on obligate seeders in eastern Mediterranean woodlands. Issue 1 (11th December 2018) - Tsafrir, Anat; Osem, Yagil; Shemesh, Hagai; Carmel, Yohay; Soref, Chanoch; Ovadia, Ofer
Abstract: Aim: Plant species regenerate after fire either through vegetative growth (i.e., obligate resprouters) or seed germination (i.e., obligate seeders), with some species adopting both strategies (i.e., facultative seeders). Fire season can have important consequences for the relative abundance of plant species adopting these regeneration strategies. The present study aimed to test for differential effects of fire season on perennial plant community composition. Location: Eastern Mediterranean woodland in the Judea Mountains, Israel. Methods: We conducted, for the first time, a large‐scale field experiment, involving prescribed spring and autumn burns in a typical eastern Mediterranean woodland. We sampled the perennial plant community before and after the burns, quantifying temporal changes in community composition caused by seasonal fires. Results: Although fire intensity and severity were consistent between the two seasonal fires, plant community composition differed between areas subjected to spring or autumn burns. The abundances of all common species, Pistacia lenticus (obligate resprouter), Cistus spp. (obligate seeders) and Teucrium divaricatum (facultative seeder), were all reduced by both fires. Yet, their dominance in the post‐fire perennial plant community was retained. Differential fire season effects were detected only among obligate seeders, which experienced a stronger reduction in abundance after spring than after autumn burns. Conclusions: Differential fire season effects on the perennial plant community resulted from phenological rather than fire intensity/severity effects. Such changes in community composition may have important implications for plant community dynamics, because they affect the circle of "fire event–plant regeneration–fire reoccurrence", determining the probability and intensity of future fires. Furthermore, even though the eastern mediterranean ecosystem is considered highly resilient to disturbances, increased spatio‐temporal variation in fire season, may result in a new vegetation mosaic, differing from the contemporary one, i.e., an alternative stable state. Abstract : Perennial plants regenerate after fire through vegetative growth or seed germination. By carrying out prescribed spring and autumn burns, in a typical eastern Mediterranean woodland, we illustrate that fire season differentially influence the seeder species, altering the composition of the entire perennial plant community. Hence, variation in seasonal fires can play a key role in maintaining biodiversity in this ecosystem.